2015
DOI: 10.1002/hep.27981
|View full text |Cite
|
Sign up to set email alerts
|

Presence of diabetes mellitus and steatosis is associated with liver stiffness in a general population: The Rotterdam study

Abstract: Given that little is known about the prevalence of, and factors associated with, liver fibrosis in the general population, we aimed to investigate this in a large, well-characterized cohort by means of transient elastography (TE). This study was part of the Rotterdam Study, a population-based study among individuals 45 years. All participants underwent abdominal ultrasound and TE. Liver stiffness measurement (LSM) 8.0 kilopascals (kPa) was used as a cutoff suggesting clinically relevant fibrosis. Of 3,041 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
246
9
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(311 citation statements)
references
References 58 publications
40
246
9
4
Order By: Relevance
“…A community based study from the Netherlands using a transient elastography reading of ≥8 kPa for the diagnosis of liver fibrosis estimated that clinically significant fibrosis was present in 5.6% (169 of 3,041) of total, nonselected individuals and 8.4% (69 of 822) of those with NAFLD, and was positively associated with steatosis and T2DM 37 . In this respect, the influence of T2DM on risk of progressive NAFLD is sup ported by a UK based paired biopsy study that showed incident T2DM to be the strongest predictor of progres sive disease 38 .…”
Section: Nafld In Europementioning
confidence: 99%
“…A community based study from the Netherlands using a transient elastography reading of ≥8 kPa for the diagnosis of liver fibrosis estimated that clinically significant fibrosis was present in 5.6% (169 of 3,041) of total, nonselected individuals and 8.4% (69 of 822) of those with NAFLD, and was positively associated with steatosis and T2DM 37 . In this respect, the influence of T2DM on risk of progressive NAFLD is sup ported by a UK based paired biopsy study that showed incident T2DM to be the strongest predictor of progres sive disease 38 .…”
Section: Nafld In Europementioning
confidence: 99%
“…[160][161][162]. In particular, the Rotterdam study conducted with transient elastography in 3041 participants found that the combined presence of T2D and steatosis was strongly associated with liver stiffness (8.0 kPa), suggestive of clinically relevant fibrosis [161].…”
Section: Role Of Lxr In Hepatic Inflammationmentioning
confidence: 99%
“…These results may suggest that the toxic injury was more severe and prolonged and the severity of ACP was more advanced in the ACP patients with liver fibrosis group [32,33]. Moreover, DM may induce steatohepatitis, which may act synergistic ally with alcohol to result in the liver parenchyma alterations and the TE findings [34,35]. DM was more frequent in our ACP patients than in a previous study [6] and this may explain the higher rate of ALF in our study as compared to the previous results.…”
Section: Discussionmentioning
confidence: 99%